Pelatihan Penyambungan Kabel Tegangan Menengah 20 KV - Syafriyudin Abubakar (Journal of Appropriate Technology for Community Services, 2021)
A reliable electric power system is needed in distributing electrical energy to customers, in the process of distributing electrical energy, interference in its distribution cannot be avoided, in general, electrical disturbances occur in underground channels, disturbance areas that are prone to and often occur usually at cable connections (Jointing). On cables that are insulated, the emergence of heat is something that must be considered. The current capacity of a cable is influenced by the characteristics of the cable components. Overheating will damage the insulation material and reduce the service life of the cable. The connection process must use the right and correct equipment and materials, to avoid insulation failure in the connection due to excessive heating on the connection which will result in a short circuit which will result in a shutdown of the electrical system. Increasing the skills of workers in the electricity sector is needed to reduce the risk of failure in the electrical system.Key words: cable jointing, insulation failure, skills